The Administrative Law. A canonical Challenger for XXI Century - Rodríguez Torrente, Jesús (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The aim of this article is to bring us closer to Administrative Law in the canon field. The current critical conception of the human being, the effect of the individual acts on the common good and a change in the defense and protection of human rights, invite us to deal with the protection and the rights of the faithful in the Church in depth, the hierarchical relations and the way to proceed through administrative channels. It consists of five parts, where we will briefly present the relation between crisis of identity, individuality and right; the importance of Vatican II and its influence on the administrative field; the reason for the administrative function in the Church. The Administrative Law in the heart of the Church, and the future challenges for current understanding.
Keywords: administrative law; acts; appeals and adminitrative aourts; hierarchy; person; pastoral